808‐nm‐Light‐Excited Lanthanide‐Doped Nanoparticles: Rational Design, Luminescence Control and Theranostic Applications. Issue 18 (10th March 2017) - Liu, Bei; Li, Chunxia; Yang, Piaoping; Hou, Zhiyao; Lin, Jun
Abstract : 808 nm‐light‐excited lanthanide (Ln 3+ )‐doped nanoparticles (LnNPs) hold great promise for a wide range of applications, including bioimaging diagnosis and anticancer therapy. This is due to their unique properties, including their minimized overheating effect, improved penetration depth, relatively high quantum yields, and other common features of LnNPs. In this review, the progress of 808 nm‐excited LnNPs is reported, including their i) luminescence mechanism, ii) luminescence enhancement, iii) color tuning, iv) diagnostic and v) therapeutic applications. Finally, the future outlook and challenges of 808 nm‐excited LnNPs are presented. Abstract : 808‐nm‐excited lanthanide (Ln 3+ )‐doped nanoparticles (LnNPs) hold great promise for a wide range of applications, spanning from bioimaging diagnosis to anticancer therapy. In this review, we present a comprehensive evaluation of the luminescence mechanism, luminescence enhancement, color tuning, and theranostic applications of 808‐nm‐excited LnNPs for the first time.